Allelic Variation of Hd17 for Rice Heading Date is Caused by Natural Selection - Zifeng Yang; Yun Li; Jin Liu; Shuiqing Wu; Xuelin Wang; Min Guan; Yanyun Li; Haitao Zhu; Guifu Liu; Shaokui Wang; Guiquan Zhang (Rice)
Abstract Heading date is an important agronomic trait of rice, which directly determines adaptability and yield. Selection for natural variated alleles for heading date genes is an important manifestation of rice domestication that allows rice to spread to more broad geographic areas. In this study, three alleles of the Hd17 gene for heading date were identified by sequence analysis of 14 single-segment substitution lines, 6 wild rice species, and 2524 accessions of O. sativa. The Hd17-1 allele is an ancestral type with a middle heading date. The Hd17-2 allele was caused by the functional nucleotide polymorphism (FNP) of C to T at position 1016 of the gene and exhibits delay heading. The Hd17-3 allele was caused by the FNP of C to T in 1673 point of the gene and shows earlier heading. The Hd17-1 allele is mainly distributed in tropical regions, carrying by 5 wild rice species, O. glaberrima, and two O. sativa (Aus/Boro and tropical japonica types). The Hd17-2 allele is mainly distributed in subtropical regions, carrying by O. meridionalis, O. rufipogon, and two O. sativa (indica subspecies and Basmati/Sandri types). The Hd17-3 allele is mainly distributed in temperate regions, carrying only by temperate japonica of O. sativa. Hd17-2 and Hd17-3 had been evolved from Hd17-1, independently. Three different rice growing regions formed three alleles of Hd17, showing that the allelic variation of Hd17 is the result of natural selection. We also found that Hd17 controls heading date by up-regulating Ghd7 and down-regulating Ehd1 under long day conditions. Our findings will help to understand the evolution and the regulation of Hd17 in rice.